Analisis Peyorasi dalam Novel Tuhan Izinkan Aku Menjadi Pelacur Karya Muhidin M. Dahlan - Katharina Woli Namang; Ahwa (Jurnal Pustaka Cendekia Pendidikan, 2025)
Semantic is the study of meaning. Changes in meaning are included in the study of semantics. These changes are influenced by the development of times caused by several factors. Changes in meaning can also occur in the world of literature, as literature is created using the medium of language. Language is a social creation, and one of the literary works is the novel. The novel Tuhan Izinkan Aku Menjadi Pelacur by Muhidin M. Dahlan is an intriguing work as its story is based on the real-life events of a devout Muslim woman who eventually becomes a prostitute. The aim of this research is to analyze the forms of pejorative meaning changes in the novel Tuhan Izinkan Aku Menjadi Pelacur by Muhidin M. Dahlan. The research method used is descriptive qualitative research. The data for this study consists of words taken from quotes in the novel, with the source being the novel Tuhan Izinkan Aku Menjadi Pelacur, published in 2016. The data collection technique employed in this research involves reading and noting by marking words that fall under pejoration, coding them, and recording the data. For the data analysis technique, the study classifies data that includes changes in pejorative meaning, analyzes the data, and draws conclusions. The results of this research found 19 forms of words that have undergone pejorative meaning changes.